مصالي الحاج خارج الثورة، ماذا حدث - بوكروبة, محمد (University of Eloued جامعة الوادي, 2020)
" أبو الوطنية " هكذا يلقب المؤرخون مصالي الحاج، زعيم حزب الشعب، وقائد النضال الحزبي ضد الفرنسيين، والمنادي بالاستقلال التام وجلاء الجيش الفرنسي من كامل التراب الوطني، مع انكار الادماج والاندماج. حيث يعتبر مصالي الحاج مدرسة وطنية تخرج منها معظم قادة الثورة في الجزائر، إلا أنه يصنف في أدبيات الثورة "خائنا" بعد تأخره عن الاعتراف بالثورة ثم عدم الانضمام اليها. صاحب مقولة "هذه الأرض ليس للبيع" في حين كان نظراءه في الحركة الوطنية لا تتعدى مطالبهم مجرد الاصلاح أو الادماج. يهدف بحثنا على إلقاء الضوء على هذا الجزء المظلم من تاريخ هذا الشخص، وكيف تحول من زعيم مغاربي إلى خائن وطني عند بعض المتكلمين عنه ؟ وهل حقا كان خائنا ومغيرا لمبادئه، أم أنها مقتضيات سياسية و عثرة تاريخية؟ Abstract Father of patriotism "Thus, historians nicknamed Masali al-Haj, leader of the Popular Party, leader of the political struggle against the French, who advocated total independence and the departure of the French army from the whole of national territory, while denying integration. Masali Haj is considered a national school from which most of the leaders of the Algerian revolution came, but he is classified in the literature of the revolution as a "traitor" after his belated recognition of the revolution and not to adhere to it. His adage "this land is not for sale" while his counterparts in the national movement did not exceed their requirements, whether reform or integration. Our research aims to shed light on this dark part of the history of this person and how has he transformed from a Maghreb leader into a national traitor? Was it really a traitor and a change in its principles, or was it a political requirement and a historic stumbling bloc
/masali Hajj Outside The Revolution! What Happene
مقال
Keywords: مصالي الحاج ; الحركة الوطنية الجزائرية ; جبهة التحرير الوطني ; ثورة التحرير ; FLN ; MNA ; MASALI HAJJ ; Revolution of national liberatio